Dr. B.R. Ambedkar’s Vision of Indian Polity: Equality, Justice, and Social Transformation - Chaudhary, Pramod Kumar (Integrated Journal for Research in Arts and Humanities, 2022)
Dr. B. R. Ambedkar, a well-known social activist as well as distinguished philosopher, was genuinely worried regarding the situation of the marginalised at the start of his distinguished career. He spent his whole life working to improve social and economic circumstances. Ambedkar's transformative vision directs individual's efforts as assists with renegotiating issues, particularly the collapse of modern political thought. Ambedkar became well-known as a key strategic philosopher throughout today's society following the rise of the dalit struggle. He rose to prominence in India's sociopolitical environment during the 1920s. With terms of political, economic, social or religious views, he was crucial to the improvement of the least rung of so-called indestructible Indian community. Furthermore, he was a brilliant sociologist, economist, judicial analyst, educationist, author, legislator, advocate, or rights-based activist. He was an iconoclast as well as researcher who successfullly organised, emancipated, or united the uneducated Indians opposing all forms of societal and political tyranny. This investigation captures Ambedkar's views on politics.